SISTEM PENGENDALIAN TOPIK DALAM WACANA PEDAGOGI DI SEKOLAH DASAR - N Lia Marliana (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research is to obtain information about the topics control system as part of textual characteristics in pedagogic discourse in elementary school in Bogor. This research uses qualitative descriptive method with content analysis technique. Data were obtained through recording technique of learning process in three schools in Bogor. The focus of this research is on the control system of teacher topics through teacher inquiries, use of greetings, use of word markers, ignoring student responses, and strengthening student responses. The structure of pedagogical discourse in the classroom consists of new lessons, transactions, exchanges, movements, and new movements. The lesson consists of transactions that are composed again on several exchanges. The movement is composed of several exchanges. Movement consists of several types of behavior: starters, responses, questions, and answers/follow-up. This research has resulted that teachers are always in control of the topic of conversation. This can be seen from the topics raised in the form of questions or statements of teachers and neglect student responses or answers by teachers. Thus, it can be concluded that students seem to obey the teacher-student discourse structure in the classroom. Whereas what happens is the dominance of teachers to students in the classroom. Research on the text dimension of pedagogical discourse is useful for teachers to improve teaching methods that are still centered on teachers and use alternative learning strategies that enable students in the classroom. Keywords: pedagogic discourse structure, topics control system, elementary school Abstrak Tujuan penelitian ini untuk memperoleh informasi mengenai sistem pengendalian topik sebagai ciri tekstual dalam wacana pedagogi di sekolah dasar di Bogor. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik analisis isi. Data diperoleh melalui teknik rekam catat proses pembelajaran di tiga sekolah di Bogor. Fokus penelitian ini ialah pada sistem pengendalian topik guru melalui pertanyaan guru, penggunaan kata sapaan, penggunaan kata penanda/pemarkah, pengabaian respons siswa, dan penguatan respons siswa. Struktur wacana pedagogi di dalam kelas terdiri atas pelajaran, transaksi, pertukaran, gerakan, dan gerakan baru. Pelajaran terdiri atas transaksi yang tersusun lagi atas beberapa pertukaran. Gerakan tersusun dari beberapa pertukaran. Gerakan terdiri atas beberapa jenis tingkah laku, yaitu pemulai, respons, pertanyaan, dan jawaban/tindak lanjut. Penelitian ini menghasilkan bahwa guru selalu mengendalikan topik pembicaraan. Hal ini terlihat dari topik yang dikemukakan berupa pertanyaan atau pernyataan guru dan pengabaian respons siswa atau jawaban siswa oleh guru. Dengan demikian, dapat disimpulkan bahwa siswa seolah-olah mematuhi struktur wacana guru-siswa di dalam kelas. Padahal yang terjadi ialah adanya dominasi guru terhadap siswa di dalam kelas. Penelitian mengenai dimensi teks wacana pedagogi ini bermanfaat bagi guru agar dapat memperbaiki metode pembelajaran yang masih berpusat pada guru dan menggunakan alternatif strategi pembelajaran yang mengaktifkan siswa di kelas. Kata kunci: struktur wacana pedagogi, sistem pengendalian topik, sekolah dasar